The impacts of tourism experiences in the destination impact. The case of the Algarve - Matos, Nelson (2011)
To succeed nowadays, tourism destinations must differentiate and create a competitive positioning, and this can only be done by addressing and adapting to the needs of their visitors. A value-attainment construct based on tourism experiences is proposed for the product development and promotion strategy of the destination Algarve.